A nondegenerate Vuong test - Xiaoxia Shi (Quantitative Economics, 2015)
In this paper, I propose a one-step nondegenerate test as an alternative to the classical Vuong (1989) tests. I show that the new test achieves uniform asymptotic size control in both the overlapping and the non-overlapping cases, while the classical Vuong tests do not. Meanwhile, the power of the new test can be substantially better than the two-step classical Vuong test and is not dominated by the one-step classical Vuong test. An extension to moment-based models is also developed. I apply the new test to the voter turnout data set of Coate and Conlin (2004) and find that it can yield model comparison conclusions different from those of the classical tests. The implementation of the new test is straightforward and can be done using the MATLAB and STATA routines that accompany this paper.
Keywords: 330; Asymptotic size; model comparison; nonnested models; voter turnout; Vuong test